Online Marketing Communication Strategy on Purchase Decisions of Dexskin Skincare Products via Instagram in Tangerang - Mega Sri Wahyuni; Komarun Zaman; Nur Aini Anisa (INCOME: Innovation of Economics and Management, 2025)
This study explores the online marketing communication strategy of Dexskin by Derma Express through Instagram in influencing consumer purchasing decisions in Tangerang. The research is motivated by the rapid growth of Indonesia’s skincare industry and the increasing demand for transparency, credibility, and educational value in brand communication. Using a qualitative descriptive approach, data were collected through observation, interviews with ten informants, and documentation of Dexskin’s Instagram marketing activities conducted between January and April 2025. The analysis draws on the STP (Segmentation, Targeting, Positioning) and AIDA (Attention, Interest, Desire, Action) frameworks to examine how Dexskin integrates educational content, visual storytelling, and collaborations with influencers and dermatologists. The findings indicate that Dexskin’s hybrid strategy—combining medical credibility and influencer relatability—tends to enhance consumer engagement, trust, and purchase intention. Educational posts foster interest and credibility, while influencer collaborations attract attention and emotional resonance. However, given the qualitative and context-specific nature of this study, the results should be viewed as exploratory rather than conclusive. Limitations include the small sample size and focus on one geographic area (Tangerang). Future research is encouraged to adopt mixed or comparative methods across multiple platforms and regions to validate and extend these insights.